Mechanisms of proteinuria in human glomerulonephritis. - Myers, B D (1982)
We evaluated glomerular barrier function in 28 patients with glomerulonephritis. Neutral dextrans of graded size were used to characterize the size-selective properties of the barrier. Charge selectivity was characterized by electrofocusing excreted urinary proteins. A fractional IgG clearance (relative to freely permeable inulin), smaller or greater than 100 x 10(-5) was used to distinguish patients with minor (group I, n = 13) and major (group II, n = 15) urinary IgG leakage, respectively. Fractional clearances of smaller dextrans (radii 20-50 A) were similar, but those of larger dextrans (radii 52-60 A) were elevated in group II relative to group I patients. A model of solute transport through a bimodal pore size distribution revealed the values for pore radius in the lower mode to approximate 51-55 A in both group I and group II patients. Pore radius in the upper mode, by contrast, was much larger in group II than in group I patients, approximating 87-97 vs. 72-77 A, respectively. Electrofocusing of urinary protein from group I patients revealed mostly albumin (isoelectric point 5.2). In group II patients, however, immunoglobulin excretion was copious. Moreover, the distribution of anionic, neutral, and cationic species (isoelectric points 5.5-8.5) in urinary and plasma eluates of IgG2 and IgG4 was similar. We conclude that when glomerulonephritis is associated with selective albuminuria, as in group I,, there is an isolated reduction of electrostatic retardation of relatively small anionic proteins. Major urinary IgG leakage (group II), however, appears to result from the development in the glomerular membrane of a subpopulation of enlarged pores that are highly permeable towards proteins of large size and varying charge.